Increased functional connectivity of white-matter in myotonic dystrophy type 1 - Li, Jing; Li, Jie; Huang, Pei; Huang, Li-Na; Ding, Qing-Guo; Zhan, Linlin; Li, Mengting; Zhang, Jiaxi; Zhang, Hongqiang; Cheng, Lulu; Li, Huayun; Liu, Dong-Qiang; et al. (Frontiers in Neuroscience, 2022)
Background: Myotonic dystrophy type 1 (DM1) is the most common and dominant inherited neuromuscular dystrophy disease in adults, which involved in multiple organs including the brain. Although structural measurements showed that DM1 is predominantly associated with white-matter damage, they failed to reveal the dysfunction of the white-matter. Recent studies have demonstrated the functional activity of white-matter is of great significance and has given us insights in revealing the mechanisms of brain disorders. Methods: Using resting-state fMRI data, we adopted a clustering analysis to identify the white-matter functional networks and calculated functional connectivity between these networks in 16 DM1 patients and 18 healthy controls (HCs). Two-sample t-test was conducted between the two groups. Partial correlation analyses between the altered white-matter FC and clinical MMSE or HAMD scores were performed. Results: We identified thirteen white-matter functional networks by a clustering analysis. These white-matter functional networks can be divided into three-layers network (superficial, middle, and deep) according to their spatial distribution. Compared to HCs, DM1 patients showed increased FC within intra-layer white-matter networks and inter-layer white-matter networks. For intra-layer networks, the increased FC was mainly located in inferior longitudinal fasciculus network, prefrontal cortex network and corpus callosum network. For inter-layer networks, the increased FC of DM1 patients mainly located in superior corona radiata network and deep network. Conclusion: Results demonstrated the abnormalities of white-matter functional connectivity in DM1 located in both intra-layer and inter-layer white-matter networks and suggested that the pathophysiology mechanism of DM1 may be related to the white-matter functional dysconnectivity.